(3GdeONd aj JNWjW Gdfbd GdMVQj s - (3UHGM eMehO(B, (3eMeOs ((3YeGf(B:s (3eDSSI GdhQGb(B,s, 2002)
(3Gdfbd aj GdYGUeI GdMOjKI,JNWjW Gdfbd aj efGWb GdeOf GdcHQi,GdMGSHGJ hJNWjW Gdfbd GdMVQj,Gdfbd OGNd GdeOf,GdeTGcd GdJNWjWjI aj GdeOf,eONd Edi SdGeI GdWQb GdMVQjI,JNWjW Gdfbd GdMVQj aj OhdI bWQ,JNWjW Gdfbd GdMVQjs
Keywords: (3GdehGUdGJs; (3Gdfbds; (3Gdfbd GdMVQj(B- (3bWQs